2009
DOI: 10.1007/s00253-008-1848-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving the thermostability and activity of Melanocarpus albomyces cellobiohydrolase Cel7B

Abstract: Two different types of approach were taken to improve the hydrolytic activity towards crystalline cellulose at elevated temperatures of Melanocarpus albomyces Cel7B (Ma Cel7B), a single-module GH-7 family cellobiohydrolase. Structure-guided protein engineering was used to introduce an additional tenth disulphide bridge to the Ma Cel7B catalytic module. In addition, a fusion protein was constructed by linking a cellulose-binding module (CBM) and a linker from the Trichoderma reesei Cel7A to the C terminus of Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…They also stabilize irreversibly unfolding proteins by decreasing the unfolding rate (15). Although a number of studies have reported that the introduction of disulfide bridges can increase enzyme thermostability (8,(10)(11)(12)(13), they have usually introduced only one beneficial disulfide bridge. Few reports describe the introduction of multiple disulfide bridges to improve the enzyme thermostability (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They also stabilize irreversibly unfolding proteins by decreasing the unfolding rate (15). Although a number of studies have reported that the introduction of disulfide bridges can increase enzyme thermostability (8,(10)(11)(12)(13), they have usually introduced only one beneficial disulfide bridge. Few reports describe the introduction of multiple disulfide bridges to improve the enzyme thermostability (9).…”
mentioning
confidence: 99%
“…The engineering of disulfide bridges is a promising strategy for improving thermostability that has created stabilized enzymes such as cellobiohydrolases (8,9), lipases (10,11), and xylanases (12,13). Disulfide bridges stabilize proteins undergoing reversible unfolding by decreasing the main-chain entropy of their unfolded states (14).…”
mentioning
confidence: 99%
“…Figure 6 shows a general shape of the spectra at 25°C, which is characteristic of β-class proteins, comparable to the secondary structure of other cellulases (Voutilainen et al 2009;Colussi et al 2012). The far UV CD spectra of both constructs did not display a negative band around 222 nm, indicating a relatively low content of α-helices (Fig.…”
Section: Circular Dichroismmentioning
confidence: 94%
“…While published impacts of CBM addition on enzyme thermostability vary, earlier studies demonstrate the potential of CBMs from thermophilic organisms to increase the thermostability of appended catalytic domains [40,41]. Accordingly, to evaluate the effect of the CtCBM3 module on AnAXE stability, the half-life of AnAXE at 60 • C was used to as a baseline to study impacts of the CtCBM3 fusion.…”
Section: Ph Optimum and Temperature Stabilitymentioning
confidence: 99%